Miejsca pamięci. O poznańskiej synagodze przy Wronieckiej. Joanna Roszak: Słyszysz? Synagoga. Wychodząc spod poznańskiej synagogi przy Wronieckiej. Lublin–Warszawa, Instytut Slawistyki PAN – Ośrodek „Brama Grodzka – Teatr NN”, 2015, ss. 140 - Nowicka, Daria (Narracje o Zagładzie [czasopismo zamknięte], 2016)
Memory Places. On the Synagogue in Poznań in Wroniecka Street. Joanna Roszak: Słyszysz? Synagoga. Wychodząc spod poznańskiej synagogi przy Wronieckiej. Lublin–Warszawa, Instytut Slawistyki PAN – Ośrodek „Brama Grodzka – Teatr NN”, 2015, ss. 140. Joanna Roszak’s book, Słyszysz? Synagoga. Wychodząc spod poznańskiej synagogi przy Wronieckiej, is a collection of commentaries and the author’s conversations with the witnesses of the bygone Jewish past, whose central place was the old synagogue in Poznań. As this review shows, the main axes of the book are memory and place, but also compassion, which are mentioned among others by Zygmunt Bauman, Baruch Bergman, Wojciech Wilczyk and Tomasz Pietrasiewicz. Through these conversations, the author points to various formulations of the memory place. She notes that the synagogue is perceived multidimensionally: firstly it is a historical site, secondly it is a space of anthropological experience, and finally it is still a place of a singular, individual sensation.